1985
DOI: 10.1104/pp.77.3.676
|View full text |Cite
|
Sign up to set email alerts
|

Control of Seed Germination by Abscisic Acid

Abstract: The physical mechanism of seed germination and its inhibition by abscisic acid (ABA) in Brassica napus L. was investigated, using volumetric growth (= water uptake) rate (dV/dt), water conductance (L), cell wall extensibility coefficient (m), osmotic pressure (IIi), water potential (*i), turgor pressure (P), and minimum turgor for cell expansion (Y) of the intact embryo as experimental parameters. dV/dt, Hi, and *i were measured directly, while m, P, and Y were derived by calculation. Based on the general equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
1
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(58 citation statements)
references
References 13 publications
4
52
1
1
Order By: Relevance
“…The effect of increasing ABA concentrations on germination of rape seed was very similar to that of decreasing if, resulting in a linear interaction between inhibition of germination by ABA and by reduced 4I (20). Subsequent work on rape seed showed that the effect of ABA was to increase the minimum 42p for growth and decrease the proportionality constant between growth rate and 4,p (extensibility coefficient) (21).…”
mentioning
confidence: 76%
“…The effect of increasing ABA concentrations on germination of rape seed was very similar to that of decreasing if, resulting in a linear interaction between inhibition of germination by ABA and by reduced 4I (20). Subsequent work on rape seed showed that the effect of ABA was to increase the minimum 42p for growth and decrease the proportionality constant between growth rate and 4,p (extensibility coefficient) (21).…”
mentioning
confidence: 76%
“…Groot and Karssen (1992) showed that ABA inhibits mechanical weakening of the tomato endosperm cap, but we found no inhibition of mannanase activity at a time when seeds that were allowed to imbibe in water would have completed radicle emergence. It is possible that endosperm weakening occurred but that embryo growth was inhibited by ABA (Schopfer and Plachy, 1985). However, initial radicle protrusion is not prevented by ABA in seeds from which the endosperm cap is removed Toorop et al, 1996), and other data also indicate that ABA action is primarily on the endosperm (Groot and Karssen, 1992;Hilhorst and Downie, 1996).…”
Section: T5 Seeds Cerminating At Reduced +mentioning
confidence: 96%
“…In many plant tissues, ABA levels rise as a result of water deficit (for review, see 31) and this has been shown to modulate the levels of mRNAs encoding proteins associated with water stress (4,11,12,20). In young embryos, however, it is the rise in ABA level itself that inhibits water uptake, probably by restricting cell wall extensibility (29), and regulation of gene expression in young embryos may be a result of water limitation, rather than a direct effect of ABA (9).…”
Section: Discussionmentioning
confidence: 99%